MODERN TECHNOLOGIES FOR TEACHING ANATOMY TO FUTURE DOCTORS IN A DIGITAL LEARNING ENVIRONMENT (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article explores the integration of modern digital technologies into the teaching of anatomy for future physicians within a digital learning environment. It highlights the transition from traditional cadaver-based instruction to virtual simulations, 3D anatomical modeling, and interactive e-learning platforms. The paper discusses pedagogical advantages of these tools, including enhanced visualization, individualized learning, and active student engagement through methods such as problem-based learning and flipped classrooms. Furthermore, the role of simulation-based education, mobile applications, and artificial intelligence in improving anatomical comprehension and clinical readiness is examined. The article also addresses the challenges in implementing digital technologies and emphasizes the need for strategic faculty training and infrastructure development. Ultimately, the study underlines that digitally enhanced anatomy education not only modernizes medical training but also better prepares students for technology-driven clinical practice.